Lactobacillus acidophilus Antimicrobial Peptide Is Antagonistic to Aeromonas hydrophila - Akter, Nahid; Hashim, Roshada; Pham, Huy Quang; Choi, Seung-Dae; Lee, Dong-Woo; Shin, Jae-Ho; Rajagopal, Kammara (Frontiers in Microbiology, 2020)
We identified an antimicrobial peptide (AMP) from Lactobacillus acidophilus that was antagonistic to Aeromonas hydrophila. In vitro studies such as well diffusion and field trials revealed that the AMP was active against A. hydrophila. The field trials of AMP using A. hydrophila-infected Channa striatus with a mannone oligosaccharide (MOS) prebiotic, A. hydrophila antigens, A. hydrophila-infected fish serum, L. acidophilus, and Lactobacillus cell free-supernatant (LABS-CFS) on an indicator organism further revealed that the antimicrobial agent could protect C. striatus. Other than the AMP, none of the above were able to eliminate the infectious agent A. hydrophila and were only able to delay the death rate for 3–4 days. Thus, we conclude that the AMP is antagonistic to A. hydrophila and may be used for the treatment of A. hydrophila infections. Subsequent L. acidophilus whole-genome sequence analyses enabled an understanding of the (probable) gene arrangement and its location on the chromosome. This information may be useful in the generation of recombinant peptides to produce larger quantities for treatment.